2018
DOI: 10.1093/aob/mcy193
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of floral volatiles in response to increasing drought stress

Abstract: Background and Aims Flowers emit a wide range of volatile compounds which can be critically important to interactions with pollinators or herbivores. Yet most studies of how the environment influences plant volatiles focus on leaf emissions, with little known about abiotic sources of variation in floral volatiles. Understanding phenotypic plasticity in floral volatile emissions has become increasingly important with globally increasing temperatures and changes in drought frequency and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 68 publications
(108 reference statements)
4
101
1
Order By: Relevance
“…In line with our expectation and previous studies (e.g., Pigliucci, 2001;Nicotra et al, 2010;Raabova et al, 2011;Campbell et al, 2019), we detected many significant effects of target climate indicating high phenotypic plasticity in majority of the traits. This indicates that the plasticity is more important than genetic differentiation for most of the traits measured in this study.…”
Section: Effect Of Target Climatesupporting
confidence: 93%
“…In line with our expectation and previous studies (e.g., Pigliucci, 2001;Nicotra et al, 2010;Raabova et al, 2011;Campbell et al, 2019), we detected many significant effects of target climate indicating high phenotypic plasticity in majority of the traits. This indicates that the plasticity is more important than genetic differentiation for most of the traits measured in this study.…”
Section: Effect Of Target Climatesupporting
confidence: 93%
“…Modeling curves of VOC emission in response to abiotic stresses is therefore challenging. The chemical analysis of the scent of flowers exposed to heat and drought revealed complex bouquets, where some compounds showed positive and negative linear changes in response to the stress, whereas others exhibited loose and unpredictable trends (Farré‐Armengol et al ., ; Campbell et al ., ; see also Table ). Field measurements of floral VOC emissions in response to abiotic stresses are relatively well documented (Farré‐Armengol et al ., , ; Burkle & Runyon, ), although the molecular and biochemical mechanisms controlling for these changes are mostly unknown.…”
Section: Abiotic Stresses and Flower Specialized Metabolism: Color Anmentioning
confidence: 85%
“…Studies conducted in petunia revealed transcriptional down‐regulation of enzymes of the phenylpropanoid and shikimate pathways and up‐regulation of their negative transcriptional repressors (Cna'ani et al ., ), leading to reduced VOC emission in response to heat (Sagae et al ., ). Through the course of evolution, floral emission of VOCs has been optimized to meet the requirements of temperature and rainfall typical of the blooming season of a given species (Farré‐Armengol et al ., ; Campbell et al ., ). Therefore, transcriptional and post‐transcriptional adjustments are expected to occur to cope with circumstances that interfere with this process.…”
Section: Abiotic Stresses and Flower Specialized Metabolism: Color Anmentioning
confidence: 97%
“…Additionally, we sampled 20 ambient air controls both inside and outside of the field greenhouse. We measured soil moisture using a time-domain reflectometry probe (FieldScout TDR 100, Spectrum Technologies, Aurora, Illinois) as a covariate (Campbell et al, 2019). We sampled mirid addition and mirid-free control plants between 4 July and 17 July, 10 days after mirid addition.…”
Section: Mirid Effects On Host Plant Volatilesmentioning
confidence: 99%
“…Peaks were initially identified using the NIST14 mass-spectra library with a minimum similarity search of at least 70%. We exported peak areas to Excel and used a filtering script in R (Campbell et al, 2019). The script filtered out contaminant compounds by comparing peak areas of floral samples to ambient air controls, and only plant samples that passed the criterion were used in the final dataset.…”
Section: Mirid Effects On Host Plant Volatilesmentioning
confidence: 99%